1997
DOI: 10.1097/00043426-199701000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Factor IX Inhibitors and Anaphylaxis in Hemophilia B

Abstract: Physicians treating young children with hemophilia B should be aware of the potentially life-threatening complication of anaphylaxis. Children with complete gene deletions or major derangements of the FIX gene appear to be at greater risk. Those identified by genotype as being at greater risk may need to receive their first 10-20 treatments in a medical facility equipped for handling such emergencies. Recombinant FVIIa, although not licensed for use in the United States, appears to be the most suitable treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
141
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(148 citation statements)
references
References 10 publications
7
141
0
Order By: Relevance
“…The magnitude of the antibody response was unmasked by pharmaceutical blockage of histamine release, thereby allowing animals to survive despite high production of IgE against hF.IX. Tests to detect IgE responses in patients with hemophilia have been developed, such as RAST (radioallergosorbent test) (9). However, there are no protocols for preventing or suppressing IgE formation, nor has there been an animal model that mimics this aspect of hemophilia pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of the antibody response was unmasked by pharmaceutical blockage of histamine release, thereby allowing animals to survive despite high production of IgE against hF.IX. Tests to detect IgE responses in patients with hemophilia have been developed, such as RAST (radioallergosorbent test) (9). However, there are no protocols for preventing or suppressing IgE formation, nor has there been an animal model that mimics this aspect of hemophilia pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, studies found that up to 50% of patients with F.IX inhibitors may experience potentially life-threatening anaphylactic reactions to F.IX which also preclude the subject from home treatment and severely hinder ITI protocols (3). These acute severe and systemic type I hypersensitive allergic reactions, often attributed to IgE formation, have been reported for treatment of hemophilia A and B, lysosomal storage disorders, and others (4)(5)(6)(7)(8)(9). No prophylactic protocols are currently available for prevention of these pathogenic antibody responses.…”
mentioning
confidence: 99%
“…An unwanted consequence of BP therapy is the development of immunogenic responses, which in some cases have little or no impact but in other cases affect safety significantly, with induction of infusion reactions, hypersensitivity reactions and autoimmune syndromes occurring due to cross‐reactivity of anti‐drug antibody (ADA) with endogenous counterparts of the BP 3, 4, 5, 6, and/or decreased efficacy related to neutralization of the BP's biological activity or increasing its clearance 7, 8, 9. For these reasons, immunogenic potential of a BP is determined during clinical trials by measurement and characterization of ADA that develop during treatment; in some cases, monitoring for biopharmaceutical and ADA levels may be conducted during routine use of approved BPs to guide patient care 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Although some of these patients are treatable using various protocols to induce tolerance to hFIX, 5 there is a subset of patients who do not respond and are therefore at a high risk of anaphylaxis and life-threatening hemorrhagic complications. 6,7 Any gene delivery strategy aimed at this subset of hFIX reactive patients must include a level of immune tolerance to the delivered transgene in order to attain successful long-term gene expression.…”
Section: Introductionmentioning
confidence: 99%